2013
DOI: 10.4049/jimmunol.1202487
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Deficiency Suppresses Lymphoma Growth in Mice by Modulating NK Cells, CD8 T Cells, and Myeloid-Derived Suppressor Cells

Abstract: Previously, we found that adiponectin (APN) suppresses IL-2–induced NK cell activation by downregulating the expression of the IFN-γ–inducible TNF-related apoptosis-inducing ligand and Fas ligand. Although the antitumor function of APN has been reported in several types of solid tumors, with few controversial results, no lymphoma studies have been conducted. In this study, we assessed the role of APN in immune cell function, including NK cells, CTLs, and myeloid-derived suppressor cells, in EL4 and B16F10 tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
5
20
0
Order By: Relevance
“…These findings indicate a reversal in the functional phenotype of the TAMs in apn −/− mice or at least a reduction in their capacity to promote tumor growth. In addition, the altered frequencies of NK cells, CD4 and CD8 T cells we observed are in agreement with other reports which demonstrated the importance of immune effector cells in a murine lymphoma model in apn −/− mice . In apn −/− mice inoculated with MN/MCA1 cells, we observed a smaller tumor mass with lower number of TAMs compared to WT mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings indicate a reversal in the functional phenotype of the TAMs in apn −/− mice or at least a reduction in their capacity to promote tumor growth. In addition, the altered frequencies of NK cells, CD4 and CD8 T cells we observed are in agreement with other reports which demonstrated the importance of immune effector cells in a murine lymphoma model in apn −/− mice . In apn −/− mice inoculated with MN/MCA1 cells, we observed a smaller tumor mass with lower number of TAMs compared to WT mice.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, the ability of APN to modify tumor related immune cell function has generated interest. It has been reported that altered functions of CD8 + T cells, NK cells and myeloid derived suppressive cells (MDSCs) in APN deficient mice contributed to the suppression of lymphoma growth . These findings imply that APN can modulate not only on tumor cell function but also the immune system during tumor development.…”
mentioning
confidence: 99%
“…In recent years, a new granulocytic population have been described as CD11b ϩ Gr-1 ϩ F4/80 Ϫ Ly-6c int Ly-6G hi with anti-inflammatory role in inflammation induced by tumor, also known as granulocytic myeloid-derived suppressor cells (g-MDSC or MDSC) (8,48,66). Adipo Ϫ/Ϫ mice bearing EL4 tumors have a significantly decreased recruitment of granulocytic MDSC (21). Importantly, BAL IL-6 was higher in Adipo Ϫ/Ϫ vs. WT mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although an experimental study found that adiponectin deficiency inhibits lymphoma growth in mice by regulating NK cells, CD8+ T cells and myeloid-derived suppressor cells [97], controversial data exists in the literature in relation to plasma adiponectin as potential biomarker of hematopoietic cancer from "lymphoid" origin. An increase [84,89,90], no change [20,74,84,86,91], and even a decrease in circulating adiponectin levels have been reported [75,78,85,87,88].…”
Section: Adiponectin and Hematopoietic Cancer From "Lymphoid" Originmentioning
confidence: 99%